Prognosis of Central Retinal Artery Occlusion: Local Intraarterial Fibrinolysis versus Conservative Treatment - Schmidt, Dieter P.; Schulte-Mönting, Jürgen; Schumacher, Martin (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Local intraarterial fibrinolysis (LIF) is one of several methods used in treating central retinal artery occlusion (CRAO). We investigated whether LIF is more effective than conservative methods in the treatment of CRAO.METHODS: In this retrospective study, a total of 178 patients (125 men and 53 women) with CRAO were treated at the Eye Hospital of the University of Freiburg from 1980 to 2000. The average age of the patients was 66.8 years (SD, 12 years). In group I, 116 patients were treated conservatively by anterior chamber paracentesis, massage of the globe, isovolemic hemodilution, acetazolamide, Pentoxifyllin, acetylsalicylic acid, and reduction of arterial hypertension. Some combination but not all of the mentioned conservative methods were used in the conservatively treated patients. In group II, 62 patients receiving LIF received local injection of urokinase or recombinant tissue plasminogen activator into the proximal part of the ophthalmic artery. In case of ipsilateral carotid artery occlusion or high grade stenosis (14 of 62 patients), the thrombolytic agent was administered into the internal maxillary artery.RESULTS: Among 178 patients, the CRAO was subtotal in 130 (73.0%), incomplete in 39 (21.9%), and total in nine (5.1%). Statistical calculations showed a significantly better visual acuity in group II patients, who were treated with LIF, in comparison with group I patients, who were treated conservatively (P = .0022).CONCLUSION: For patients with CRAO, LIF is superior to conservative treatment.